Pengaruh Terapi Relaksasi Otot Progresif Terhadap Insomnia Pada Lansia Posbindu Desa Patikraja - Nurita Rizkiana; Wasis Eko Kurniawan; Surtiningsih Surtiningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Insomnia is one of the main disorders in initiating and maintaining sleep among the elderly. Insomnia is defined as a complaint about a lack of quality sleep caused by one of the reasons why it is difficult to get into sleep, frequent awakenings at night and then difficulty getting back to sleep, waking up too early, and not sleeping well. The poor quality of sleep in the elderly is caused by increased sleep latency, reduced sleep efficiency and early awakening due to the aging process. The purpose of this study was to determine the effect of progressive muscle relaxation therapy on insomnia in the elderly in posbindu, patikraja village. This type of research is one group pretest-posttest with pre-experimental. The sample size used in this study was 19 respondents. The sampling technique used is purposive sampling. Methods of data collection using a questionnaire. The statistical test used in this study was the Wilcoxon Sign Rank Test with 0.05. The results of this study note that there are differences before and after being given progressive muscle relaxation therapy. The results of the analysis of the Wilcoxon Sign Rank Test obtained a p value of 0.000 <0.05, meaning that there is an effect of progressive muscle relaxation therapy on changes in insomnia in the elderly in Posbindu, Patikraja Village.